Exploring the interplay of gender, breastfeeding practices, and minimum dietary diversity on stunting among Indonesian children aged 6–23 months - Rossa Amalia; Hartati Eko Wardani; Tika Dwi Tama; Anindya Hapsari (Public Health and Occupational Safety Journal, 2025)
Background: Stunting has the highest prevalence compared to other major malnutrition problems. Risk factors for stunting include gender, breastfeeding, and complementary feeding practices. Stunting requires a faster reduction in prevalence to avoid functional losses in children. Objectives: This study aimed to determine the association between gender, early breastfeeding initiation, exclusive breastfeeding, breastfeeding status, and Minimum Dietary Diversity with the incidence of stunting. Methods: This study was an observational analytic study with a cross-sectional approach. The population of the study was children aged 6-23 months in West Java who were sampled by the Indonesian Nutrition Status Study (SSGI) 2021, and the study sample was all members of the population who met the inclusion criteria. Data in this study were obtained through SSGI 2021 documentation and analyzed using the Chi-Square and logistic regression tests. Results: The results of the bivariate analysis showed a significant association between gender (OR=1.249; 95%CI 1.013-1.540; p=0.042) and breastfeeding status (OR=0.693; 95%CI 0.533-0.901; p=0.007) with the incidence of stunting. Early breastfeeding initiation (p=0.792), exclusive breastfeeding (p=0.059), and MDD (p=0.882) had no significant association with the incidence of stunting in children aged 6-23 months in West Java. Multivariate analysis showed that the most influential factor in the incidence of stunting was gender (OR=1.260; 95%CI 1.022-1.555; p=0.031). Conclusions: This study shows the association between gender and breastfeeding status on the incidence of stunting. Further research is recommended to explore the role of complementary feeding practices and maternal nutrition in stunting prevention.